2018
DOI: 10.1016/j.myc.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ectomycorrhization of Tricholoma matsutake strains is differentially affected by soil type

Abstract: The Japanese delicacy Tricholoma matsutake has been conducted in vitro ectomycorrhizal 2 syntheses for more than 20 y. The development of its ectomycorrhizal structures varies among 3 experimental systems. Here, we examined the effects of soil-fungus interactions on the early 4 stage of in vitro T. matsutake ectomycorrhization. Axenic Pinus densiflora seedlings were 5 transplanted into autoclaved natural inorganic soil, inoculated with the cultured mycelium of T.6 matsutake, and incubated for 90 d in vitro. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…In the experiment using Koshibu soil we found a commensal effect of T. matsutake inoculation on pine growth, but no correlation between ectomycorrhizal root length and pine seedling biomass. We have consistently reported the symbiotic effect of T. matsutake on pine growth in vitro when using different soil samples (Yamada et al, 2006, Murata et al, 2013, Saito et al, 2018. The Koshibu soil experiment was the first to show a commensal effect of T. matsutake on pine growth.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In the experiment using Koshibu soil we found a commensal effect of T. matsutake inoculation on pine growth, but no correlation between ectomycorrhizal root length and pine seedling biomass. We have consistently reported the symbiotic effect of T. matsutake on pine growth in vitro when using different soil samples (Yamada et al, 2006, Murata et al, 2013, Saito et al, 2018. The Koshibu soil experiment was the first to show a commensal effect of T. matsutake on pine growth.…”
Section: Discussionmentioning
confidence: 61%
“…The dried soil was saturated with distilled water to produce a relative water content of 75%. Approximately 180 mL water was required to increase the water content to 75% for 1 kg dried soil (Saito et al, 2018). In the nitrogen-added soil treatment, 1.0 g of powdered dried yeast (Ebios, Asahi Group Foods, Ltd., Tokyo, Japan) was added to 1 L dried soil.…”
Section: Tera Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work on saffron milk cap cultivation indicates that it is possible to obtain high EMF yield from managed tree orchards. Establishing full-scale experimental EMF orchards, in which management treatments are tested statistically, is one priority for future research, as are an improved understanding of fruiting mechanisms of EMF (Le Tacon et al, 2016;Ogawa et al, 2019b), genomic and genetic studies (Martin & Bonito, 2012) aimed at elucidating fruiting mechanisms, and selecting or breeding for efficient symbionts (Saito et al, 2018;Yamada et al, 2019). The saffron milk cap yield data presented in this review can also serve as a reference for future full-scale replicated trials.…”
Section: Conclusion and Long-term Benefitsmentioning
confidence: 99%
“…The last approach of transplanting shiro to uninfected pine trees has been tried extensively in Korea ( Park et al, 2007 ). In vitro ectomycorrhization of T. matsutake has been successful ( Yamada et al, 1999 , 2006 ; Saito et al, 2018 ), but field trials showed limited production of fruiting bodies ( Ka et al, 2018 ). In order for this method to be efficient, T. matsutake must persist the pine seedling roots.…”
Section: Introductionmentioning
confidence: 99%